Innovation in paddy pest control: Education and implementation of refugia for sustainable agriculture - Mujiyo, Mujiyo; Suntoro, Suntoro; Syamsiyah, Jauhari; Dewi, Widyatmani Sih; Rahayu, Rahayu; Widijanto, Hery; Herawati, Aktavia; Herdiansyah, Ganjar; Hasanah, Khalyfah; Anggita, Akas; Irmawati, Viviana; Romadhon, Muhammad Rizky; Hardian, Tiara; Istiqomah, Nanda Mei (Community Empowerment, 2025)
Given paddy's status as a staple commodity and primary livelihood in Slogoretno Village, frequently experiencing yield reductions due to pest attacks, this community service activity aimed to educate and implement Integrated Pest Management (IPM) through the planting of refugia plants. The program involved the socialization of local-based refugia concepts, practical planting of perimeter refuge patterns on paddy demonstration plots, and the initiation of agrotourism. The results showed a significant increase in farmers' and the community's knowledge regarding ecological engineering techniques using flowering plants for paddy pest control. Furthermore, these demonstration plots have the potential to become agrotourism objects, which is expected to enhance local welfare and sustainably boost harvest productivity. The implementation of refugia affirms its effectiveness as an IPM innovation supporting sustainable agriculture.